EVALUASI PEMBELAJARAN PENJASORKES - Prilanji, Fito Bakdo; Simanjuntak, Victor Gaperius; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study was that the assessment aspects such as psychomotor, affective, and cognitive were not yet implemented, because some teachers did not design the scoring system neatly in writing, so that the evaluation conducted by the teacher was  not well planned. The purpose of the study was to find out the evaluation of physical education learning at the senior high school teachers in the city of Pontianak. The method used in this study was a descriptive method and a form of survey research. The population in this study amounted to 15 teachers. The sample used total sampling totaling 15 high school teachers in the city of Pontianak. Based on the results of the research conducted on the evaluation of penjasorkes learning classified into two categories. A very good category is 66.7%, and teachers who were included in the good category amount to 33.3%, while those included in the category were enough and less that was equal to 0%. The number of scores for all teacher groupings is 347, which means that the evaluation of physical education learning for all senior secondary school teachers in Pontianak City was included in the excellent category. Keywords:       Evaluation, Learning, Physical Education